Analysis of the Sustainability of the Economic Dimension to the Development of Halal Tourism in Banyuwangi Regency - Dini Nafisatul Mutmainah; Muksin Muksin; Sri Sundari (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2020)
Tourism with the concept of halal / sharia is a tour that implements Islamic laws in it , which aims to meet the desires of tourists . The purpose of this paper is to identify sustainability status condition, to formulate sustainable development models and scenarios , and formulate a strategy or policy development halal tourism sustainability at Banyuwangi Regency. This paper used a combination of quantitative and qualitative approaches ( mixed method ). The analytical tool used in this paper is the Multi Dimensional Scaling Analysis (MDS) to identify the condition of the status of halal tourism sustainability and Interpretative Structural Modeling (ISM) to formulate a strategy or policy for the development of halal tourism sustainability . Data obtained through the observation, surveys , expert interviews , and documentation. The results of this study indicate that the economic dimension is the most influential dimension on the sustainability of halal tourism in Banyuwangi Regency. In the MDS analysis, on the economic dimension there are two priority attributes and their RMS values, namely Halal Tourism Marketing Access (2 , 73 ) and Labor Absorption (2.68). Furthermore, in the ISM analysis, the sub-element hierarchy structure that has the strongest influence on sustainable halal tourism management at the highest level (level 4) is E8 Transparency in Policy.